Enhancing biogas production from chicken manure through vacuum stripping of digestate - AKGÜL, DENİZ; ÇALLI, BARIŞ (My University, 2023)
The vacuum stripping’s combined ammonia removal and disintegration effect on chicken manure digestate was evaluated for the first time at different pH values (8.5, 9.5, and 10.5) and temperatures (30, 50, and 70 °C). In this way, the potential increase in biogas production by recirculating the vacuum-stripped digestate to the anaerobic digester was determined. Experimental results showed that increasing pH and temperature significantly increase TAN removal, but pH is more effective. A significant portion of the ammonia was removed in the first 30 min. Therefore, a second set of stripping tests was performed for 30 min and at 70 °C and pH 10.5. After 30-min tests, a biomethane potential (BMP) assay was performed using the vacuum-stripped digestate to determine how vacuum stripping affects biomethane production. Despite having the lowest disintegration efficiency, the highest biomethane potential (56.2 ± 29.7 mL CH4/gVS) was obtained with the digestate, which was subjected to vacuum stripping at 70 ℃ without pH adjustment, and 48.7% more methane was produced than the control set. The lower residual biomethane potential in vacuum-stripped digestate at pH 9.5 and 10.5 was attributed to Na+ inhibition resulting from high NaOH consumption for pH adjustment. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENERGY & FUELS; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Renewable Energy, Sustainability and the Environment; Physical Sciences; Ammonia; BMP; Chicken manure; Methane